Transmembrane Protein-Based Risk Model and H3K4me3 Modification Characteristics in Lung Adenocarcinoma - Fan, Tao; Liu, Yu; Liu, Hengchang; Wang, Liyu; Tian, He; Zheng, Yujia; Zheng, Bo; Xue, Liyan; Li, Chunxiang; He, Jie (Frontiers in Oncology, 2022)
The role and mechanism of transmembrane proteins(TMEMs) in tumorigenesis remains unclear. Based on 4 independent cohorts containing 1208 cases, we identified 3 TMEMs (TMEM273, TMEM164, and TMEM125), which were used to construct a risk model to predict the prognosis of LUAD. The two patterns based on risk score exhibited a high degree of consistency with the characteristics of immune cell infiltration and epigenetic distribution. Patient with low risk score, characterized by increased activation of immunity, H3K4me3 modification, tumor cell apoptosis, chemokine secretion, and TMB, had better disease-free survival(DFS) and overall survival(OS). Obvious immunosuppression, increased epithelial-mesenchymal transition (EMT), low H3K4me3 level, shortened cell cycle, and accelerated cell division manifested in high-risk patients, with poorer DFS and OS. The model showed a better prognostic value than TIDE score. Correlation analysis told us that patients with high scores were suitable for treatment with CD276 inhibitors for their higher levels of CD276 expression. The risk score had a strong negative correlation with HAVCR2 and ICOS among patients with EGFR-WT, KRAS-WT, STK11-WT, or TP53-MUT, and patients with these mutation types with low scores were suitable for treatment with HAVCR2 or ICOS inhibitors. This work comprehensively analyzed the role and mechanism of TMEMs in LUAD, and revealed the characteristics of histone methylation modification. The TMEM-based signature gave us deep insight into immune cell infiltration profiles and provided an individualized immunotherapy strategy.